Sex Differences In the Enduring Neuroinflammatory and Behavioural Sequelae of Systemic Immune Challenge During Puberty - Kolmogorova, Daria (Université d'Ottawa / University of Ottawa, 2021)
Puberty is a critical period for sexual maturation during which the sex-specific reorganization and remodelling of the pubertal brain facilitate sex biases in stress sensitivity. Pubertal (i.e., six-week-old) CD-1 mice treated with the bacterial endotoxin lipopolysaccharide (LPS; 1.5 mg/kg body weight, ip) show several sex-specific changes to the neuroendocrine and behavioural systems of several reproductive and non-reproductive functions. One promising explanation for the elusive mechanisms driving the sex-specific outcomes of pubertal immune challenge may lie in the cascade of neuroimmune events induced by this systemic immune stressor. This doctoral thesis tested the hypothesis that sex-specific responses of the pubertal neuroimmune network contribute to sex differences in the enduring outcomes of pubertal immune challenge on hippocampus-dependent cognitive processes. Male and female CD-1 mice are equally vulnerable to enduring impairments in spatial memory following pubertal LPS exposure. Across brain regions for cognition and stress regulation, pubertal LPS treatment alters baseline sex differences in microglial expression and morphology in a sex-dependent manner. The temporary female-specific increase in whole-brain blood-brain barrier permeability during LPS-induced sickness may have facilitated the apparent female bias in LPS-induced changes to pubertal microglia. In the context of sex- and region-specific residual effects of pubertal LPS-induced sickness on microglial expression and morphology, pubertal LPS treatment may accelerate certain neurodevelopmental processes in males but not females. The innate sex differences in the pubertal neuroimmune network highlighted by these studies underscore how a systemic immune challenge precipitates sex biases in immune-mediated disorders of brain and behaviour during adulthood.
Keywords: Puberty; Lipopolysaccharide; Sex differences; Microglia; CD-1 mouse; Neuroinflammation; Hippocampus; Memory; Learning; Blood-brain barrier; Apoptosis; Cell development